THU0069 Ultrasound-Guided Assessement of Axillary Lymph Node Reactivity/Structural Heterogeneity in Rheumatoid Arthritis: Relationship with Disease Activity and Joint Inflammation. (23rd January 2014) - Manzo, A.; Benaglio, F.; Bugatti, S.; Vitolo, B.; Alessi, S.; Caporali, R.; Calliada, F.; Montecucco, C.
Abstract : Background: There is growing evidence in the murine system suggesting that joint-draining lymph nodes (LN) and the afferent lymphatic system are relevant patho-phisiologic components of chronic arthritis acting through the control of cell efflux, containment of peripheral inflammation and, potentially, local generation/regulation of immune responses. The draining LN-afferent lymphatic system could be therefore a complementary target for aetio-pathogenesis studies, biomarker development and novel therapeutic approaches. LN responses are coupled to structural changes that include size modifications, hypertrophy of cortical regions and vascular flow alterations. In keeping with this concept, we have previously shown that specific sub-clinical changes in LN structure can be detected in a proportion of patients with RA through non-invasive ultra-sonographic approaches (power Doppler ultrasonography-PD-US). Objectives: To evaluate the prevalence of and characterize specific PD-US axillary LN changes among RA patients in different activity phases of the disease vs healthy controls in relationship to clinical parameters, joint ultrasound scores, systemic immune- and inflammatory markers. Methods: 29 RA patients with active disease (DAS28>3.2) candidate to biologic treatment, 40 RA patients in clinical remission (DAS28<2.6 for more than 6 months) following conventional DMARDs therapy, and 20 healthy controls were recruited for the study. All patients underwent complete clinical assessment, laboratory evaluations, PD-US assessments of hands and wrists and PD-US evaluation of axillary LN bilaterally. Axillary LN were evaluated for volume (inferred by ellipsoid formula), cortex hypertrophy, vascular distribution in the ilar, medullary and cortical regions through PD analyses and semi-quantitative (0-4 point scale) evaluations of regional flow characteristics. Results: Following standardized examinations, axillary LN were ultrasonographically visualized in 86% of RA patients with active disease and 85% of healthy controls with no significant difference in the mean number of detectable LN per patient (range: 0-8 in controls vs 0-9 in RA). Despite an apparently similar anatomic substrate, RA patients with active disease and healthy controls significantly differed for specific morpho-structural LN features including median LN volume (p<0.05), vascular flow distribution (grade 3 PD score: 34% in RA vs 0% in controls, p<0.01) and prevalence of cortical hyperthrophy (p<0.05). Axillary LN PD scores showed a significant correlation with hand and wrist PD score (p<0.05). RA patients achieving DAS28 clinical remission showed reduction of morphostructural LN alterations if compared with patients with active disease, but not a systematic return to normalcy. Conclusions: RA pathologic process can involve axillary LN with specific morphostructural alterations detectable and quantifiable by PD-US. Parameters able to capture specific LN alterations in course of RA may be important to focus future basic and clinical research. Disclosure of Interest: None Declared